Phenomenological Study: Formation of Student's Honest Character Through The Honesty Canteen At SMPN 4 Nganjuk - Apriliansah, Dayu Feri; Abdul Haris; Syamsurizal Yazid (PT Inovasi Pratama Internasional, 2025)
This research aims to explore students' experiences of joining an honesty canteen and how students interpret the existence of an honesty canteen. This study was conducted at SMPN 4 Nganjuk, which used qualitative research with a phenomenological approach. Data collection techniques included observation, interviews, and documentation. The data validity test technique used member checking, and the data analysis technique used descriptive narrative phenomenology. The results of the research show that students are enthusiastic about participating in the honesty canteen. Based on their experience, the existence of the honesty canteen provides positive value and makes it easier for them to carry out transactions, train their honesty, and require them to be honest and have a sense of responsibility for the trust they have been given. The meaning of the honesty canteen for students is that the honesty canteen provides motivation, awareness, and understanding of the importance of honesty and forms their habit of always being honest and responsible